Hubungan Peran Stimulasi Orang Tua dengan Perkembangan Anak (3-4 Tahun) Kartika dan (4-6 Tahun) Dharma Wanita di Desa Meteseh - Kartini Isnaini; Kurnia Wijayanti; Nopi Nur Khasanah (Journal of Health, Medical, and Psychological Studies, 2026)
The quality of stimulation supplied by parents significantly influences early childhood development, particularly in motor, language, and personal-social domains. Nevertheless, developmental delays are still observed among a proportion of preschool children. This study aims to examine the relationship between parental stimulation and the development of children aged 3-4 years at Kartika Early Childhood Education (PAUD) and 4-6 years at Dharma Wanita Kindergarten in Meteseh Village. This study used a descriptive correlative design with a cross-sectional approach involving 60 respondents selected through a total sampling technique. The instruments used were a questionnaire assessing parental stimulation (35 items) and the Denver Developmental Screening Test (DDST) observation form. Univariate and bivariate analyses were conducted using the Spearman Rank test. The findings indicated that most parents demonstrated good stimulation practices (73.3%), while children’s developmental status was equally distributed between normal and suspect categories (50.0% each). The correlation analysis yielded a p-value of 0.567 and an r-value of 0.075, indicating a positive but very weak and statistically non-significant relationship.  This study revealed that there is no significant correlation between parental stimulation and child growth.